A Discursive Review of Intellectual Capital versus Organizational Development and Organizational Design - Mustafa M. Bodrick; Ibrahim M. Alhabib; Saleh A. Aljurbua; Mohammed I. Alassaf; Mohammed I. Alsuhaim; Almuways, Yasir S. (Journal of Psychology and Behavior Studies, 2024)
This discursive review explores the relatedness between the concepts of intellectual capital versus organizational development and organizational design. This deliberated discourse examines these concepts within the organizational contexts of business performance and related processes aligned to cultural, structural, and strategic elements of institutional capabilities. The review is framed within discursive psychology that focuses on action orientation, situational reality, and constructive engagement by questioning whether these concepts are similar, different yet related, or perhaps in fact dissimilar. Therefore, by amplifying the discourse related to these organizational concepts, the rhetorical question remains as to the importance for achieving clarity when setting out within the business context, whether it be strategic, operational, or cultural.